PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SUNSCREEN FACETOLOGY DI SHOPEE (STUDI KASUS DI KOTA BEKASI) - Aulia Uzzahro Utomo; Wastam Wahyu Hidayat; Cahyadi Husadha (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This study aims to analyze the effect of product quality, price, and brand image on purchasing decisions for Facetology sunscreen through the Shopee platform among residents of Bekasi City. This research employs a quantitative approach with a causal design. Primary data were obtained through an online questionnaire distributed to 102 respondents selected using the accidental sampling technique. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS 4.0. The results indicate that product quality, price, and brand image have a positive and significant effect on purchasing decisions. Product quality exerts the greatest influence, followed by price and brand image. The R-Square value of 0.603 indicates that the model’s predictive capability is classified as moderate. All hypotheses were accepted, indicating that improving product quality, supported by appropriate pricing and a strong brand image, can enhance consumer purchasing decisions.